Predatory publications in Scopus: Evidence on cross-country differences - Vít Macháček; Martin Srholec (Charles University in Prague, Institute of Economic Studies (IES), 2019)
The paper maps the infiltration of so-called "predatory" scholarly journals into the citation database Scopus. Using the names of "potential, possible, or probable" predatory journals and publishers on Beall's lists, we derived ISSNs of the respective journals from Ulrichsweb and searched Scopus with it. A total of 324 matched journals with 164 thousand documents indexed in Scopus over 2015-2017, making up a share of 2.8 % of the total articles have been identified. An analysis of cross-country differences in the tendency to publish in these journals reveals that overall the most affected are middle-income countries in Asia and North Africa. Kazakhstan is the country with the largest tendency to publish in predatory journals (18 %). More than 5 % is reported in 20 countries, including large countries such as Indonesia (18 %), Malaysia (11 %), India (10 %), or Nigeria (7 %). Neither developed countries are resistant to predatory publishing. More than 16 000 "potentially predatory" articles were published by authors from United States (0.67 %).
Keywords: I28; I29; O38; 330; Predatory journals; Beall's list; open access; academic misconduct